Uji Aktivitas Antibakteri Fraksi N-Heksana Daun Pepaya (Carica papaya Linn.) Terhadap Escherichia coli dan Staphylococcus aureus - Aprillia, Hananing; Putra Pratama, Nofran; Nur'Aini Purnamaningsih (JOURNAL OF PHARMACEUTICAL (JOP), 2023)
Background: Infectious diseases are still a problem for the world of health. Infectious diseases are caused by viral, bacterial and parasitic infections. Inappropriate use of antibiotics in treating bacterial infections can cause antibiotic resistance effects. Prevention of the effects of resistance can be done by looking for natural antibiotic agents derived from plants. One of the potential medicinal plants as antibiotics is papaya leaf. Objective: The objective of study was determine the antibacterial activity of the papaya leaf n-hexane fraction against Escherichia coli and Staphylococcus aureus and to determine the diameter zone of inhibition the papaya leaf n-hexane fraction at 20%; 40%; 60%; 80%; and 100% against Escherichia coli and Staphylococcus aureus. Method: Papaya leaf were extraction by using maceration method of 70% ethanol as solvent. Separation of compounds based on the level of polarity using fractionation method with n-hexane: water (1:1 v/v) solvent then carried out phytochemical screening and separation of compounds using TLC method. The antibacterial activity testing used by agar diffusion method Kirby Bauer with the treatment group of papaya leaf n-hexane fraction with a concentration of 20%; 40%; 60%; 80%; and 100%, the positive control group used Ampicillin 10 ?g and the negative control group used Aquades. Result: Diameter zone of inhibition Escherichia coli and Staphylococcus aureus was smallest at 20% was 6,57 ± 0,15 mm and 6,69 ± 0,33 mm, while the diameter zone of inhibition the largest at 100% was 7,92 ± 0,23 mm and 7,94 ± 0,16 mm. Conclusion: The papaya leaf n-hexane fraction concentration of 20%; 40%; 60%; 80%; and 100% had antibacterial activity against Escherichia coli and Staphylococcus aureus. The higher concentration then the larger diameter zone of inhibition formed.